2019
DOI: 10.1007/s00432-019-02854-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced vs. standard dose native E. coli-asparaginase therapy in childhood acute lymphoblastic leukemia: long-term results of the randomized trial Moscow–Berlin 2002

Abstract: PurposeFavorable outcomes were achieved for children with acute lymphoblastic leukemia (ALL) with the first Russian multicenter trial Moscow–Berlin (ALL-MB) 91. One major component of this regimen included a total of 18 doses of weekly intramuscular (IM) native Escherichia coli-derived asparaginase (E. coli-ASP) at 10000 U/m2 during three consolidation courses. ASP was initially available from Latvia, but had to be purchased from abroad at substantial costs after the collapse of Soviet Union. Therefore, the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
0
12
0
4
Order By: Relevance
“…23 Several types of evidence indicate that the therapeutic index of Asp is related to the duration of Asp activity above the lowest effective activity, but not the maximum activity. [22][23][24] Comparatively, for regular L-Asp, the number of doses, instead of a single dosage, was found to correlate with better efficacy and better treatment outcome. In SCMC-ALL-2005, E coli Asp was scheduled to be administered at 6000 U/m 2 every other day for eight doses; this dosing schedule was proven to be effective for most patients.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…23 Several types of evidence indicate that the therapeutic index of Asp is related to the duration of Asp activity above the lowest effective activity, but not the maximum activity. [22][23][24] Comparatively, for regular L-Asp, the number of doses, instead of a single dosage, was found to correlate with better efficacy and better treatment outcome. In SCMC-ALL-2005, E coli Asp was scheduled to be administered at 6000 U/m 2 every other day for eight doses; this dosing schedule was proven to be effective for most patients.…”
Section: Discussionmentioning
confidence: 88%
“…Increasing Asp activity by shortening the administration interval or by increasing the single dose to 3500 U/m 2 did not further increase the degree of ASN depletion in the CSF 23 . Several types of evidence indicate that the therapeutic index of Asp is related to the duration of Asp activity above the lowest effective activity, but not the maximum activity 22‐24 . Comparatively, for regular L‐Asp, the number of doses, instead of a single dosage, was found to correlate with better efficacy and better treatment outcome.…”
Section: Discussionmentioning
confidence: 94%
“…In the first study ALL MB 1991, which was carried out in a few better equipped clinics, it could be shown that the results were actually satisfactory and that acute side effects and the need for supportive therapy were significantly lower compared to a slightly modified BFM ALL 90 protocol [36]. The consecutive ALL-MB 2002 study showed that DEXA had a superior effect compared to methylprednisolone, especially in extracompartments [37], and that a single weekly administration of ASP at a dose of 5 kU/m 2 in SR patients was not inferior to 10 kU/m 2 [38]. Since the expected goal of reducing acute side effects with an acceptable rate of recurrences had already been achieved in the first studies, one of the guiding principles of the following MB studies was the possibility of further therapy de-escalation.…”
Section: Discussionmentioning
confidence: 97%
“…The cooperative Moscow-Berlin ALL studies initially were aimed at achieving favorable results with comparatively moderate treatment intensity, which could be carried out under Russian conditions [36]. Since the expected goal of reducing acute side effects and the need for supportive therapy were achieved in the first study ALL-MB 91, one of the guiding principles of the following MB studies was the possibility of further therapy de-escalation [37,38]. In study ALL-MB-2008, MFC was used for the MRD measurement in parallel to treatment [39,40], initially without drawing any consequences from these results with regard to patient stratification.…”
mentioning
confidence: 99%
“…Pneumonia was seen in about 50% of patients and hypersensitivity reaction was reported in 4.5% (n=31) patients in E. coli asparaginase 10000 arm. In E. coli 5000 arm 1.8% (n=13) patients showed hypersensitive reaction [24]. Later, 15 out of 16 deaths were for patients over 40 years.…”
Section: Toxicitymentioning
confidence: 95%